The value of parathyroid scintigraphy on lesion detection in patients with normocalcemic primary hyperparathyroidism [El valor de la gammagrafía paratiroidea en la detección de lesiones en pacientes con hiperparatiroidismo primario normocalcémico] - (:unkn) unknown (Ediciones Doyma, S.L., 2021)
Objective: Primary hyperparathyroidism (PHPT) is one of the most frequent endocrine diseases. Most of the patients with PHPT are asymptomatic, and only 20% of them become symptomatic with increasing levels of calcium. It has been reported that normocalcemic primary hyperparathyroidism (NPHPT) may be the incipient period of PHPT where calcium (Ca) levels are in normal range, and it may advance to overt PHPT. Early diagnosis of PHPT is important in order to prevent its complications. In this retrospective study, we aimed to evaluate the role of 99mTc-MIBI parathyroid scintigraphy on lesion detection in patients with NPHPT. Material and methods: The parathyroid scintigraphy database was reviewed retrospectively in patients with PHPT. 117 patients who underwent 99mTc-MIBI scintigraphy were recruited to the study. Serum calcium level above 10.5 mg/dl was considered as hypercalcemia. Results: A total of 117 patients’ (female/male:98/19) mean serum PTH levels (mean ±SD) were 149 ± 97 pg/ml in normocalcemic group (Ca:9.6 ± 0.6 mg/dL, n:38) and 189 ± 135 pg/ml in hypercalcemic group (Ca:11.4 ± 0.6 mg/dL, n:79) (p:0.072). The sex and ages were not different between the scintigraphy positive and negative groups, but the lesion detection rates with parathyroid scintigraphy were 42% in normocalcemic group and 81% in hypercalcemic group (p < 0.0001). Conclusions: Several factors including serum Ca, the imaging protocol, existence of multiglandular disease, the size and MIBI biokinetics of the adenoma may influence lesion detectability in parathyroid scintigraphy. Although high serum Ca level is an important parameter in predicting its success, parathyroid scintigraphy remains a valuable diagnostic method even in patients with NPHPT. © 2020 Sociedad Española de Medicina Nuclear e Imagen Molecular
Keywords: Calcium; Hyperparathyroidism; Parathyroid scan